Abductor Pollicis Longus: A Study of 50 South Indian Cadavers - Vollala, Venkata Ramana (Fırat University, 2007)
The abductor pollicis longus (APL) muscle has been studied bilaterally in 50 cadavers. In one of the specimens we observed an additional muscle belly arising from the lateral aspect of the distal portion of the typical abductor pollicis longus muscle unilaterally on the left side. The tendon of additional belly inserted to the abductor pollicis brevis, opponens pollicis and flexor pollicis brevis muscles. Whereas the normal APL tendon inserted to the first metacarpal bone. Morphologic features of the abductor pollicis longus muscle are important because of its role in the stabilization of the carpometacarpal joint of the thumb. The presence of such a variation could contribute to the plastic reconstructions of the hand and the clinical evaluation of thumb functions. An understanding of this unusual finding may be clinically relevant in describing the dorso-lateral compartment of the distal forearm. ©2007, Firat University, Medical Faculty

M. abductor pollicis longus 50 kadavra üzerinde bilateral olarak çalışıldı. Kadavraların bir tanesinde tek taraflı olarak, m. abductor pollicis longus distal parçasının lateral yüzünde yükselen ilave bir kas karnı gözlemledik. Bu ilave kas karnının tendonu m. abductor pollicis brevis, m. oppones policis ve m. flexor pollicis brevis kaslarına tutunmaktaydı. Oysa normal olarak m. abductor pollicis longus tendonu birinci metakarpal kemiğe yapışmaktaydı. Art. carpometacarpea pollicis'in stabilizasyonundaki rolünden dolayı m. abductor pollicis longus'un morfolojik yapısı önemlidir. Böyle bir varyasyonun varlığı el fonksiyonlarının klinik olarak değerlendirilmesi ve ele yapılacak olan plastik cerrahi yaklaşımlar açısından anlamlıdır. Bu sıra dışı bulguların bir önemi de, ön kolun distal kısmının dorsolateral kompartmanının kliniğiyle alakalı olmasıdır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
M. Abductor Pollicis Longus: Güney Hindistanlı 50 Kadavra Üzerinde Yapılan Bir Çalışma